(untitled) (Western European Journal of Historical Events and Social Science, 2024)
This article describes the empirical data of volitional activity obtained using psychodiagnostic methods of personality and gender differences. The study focuses on highlighting the personality and gender differences of volitional qualities based on the essence of the content. Recommendations for the development of power are also cited.